1998
DOI: 10.2466/pr0.1998.83.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Suicide Risk Factors among Personnel in the United States Marine Corps (Pacific Forces)

Abstract: Risk factors for suicide among active-duty members of the United States Marine Corps were investigated. Three groups were suicide attempters (n = 172), completers (n = 22), and a nonpsychiatric comparison group (n = 384). A series of multiple regression and discriminant analyses were conducted to assess whether any of 137 selected risk-factors differentiated the suicidal group from the comparison group. The following factors differentiated suicide attempters and completers from the comparison group and were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 10 publications
1
9
0
3
Order By: Relevance
“…However, the interpretation of the data has been challenged, particularly given complexities of making population‐based estimates in cities with high rates of noninhabitant visitation. The St. Louis ECA study found no association between problem/pathological gambling and suicidal tendencies in the general population, 11 and a controlled pilot study of Marines found a negative correlation between a history of gambling participation and attempted or completed suicide 12,67 . Taking the data together, the relationship between different levels and types of gambling and suicidal thoughts and behaviors is at present incompletely understood and warrants further investigation.…”
Section: Resultsmentioning
confidence: 97%
“…However, the interpretation of the data has been challenged, particularly given complexities of making population‐based estimates in cities with high rates of noninhabitant visitation. The St. Louis ECA study found no association between problem/pathological gambling and suicidal tendencies in the general population, 11 and a controlled pilot study of Marines found a negative correlation between a history of gambling participation and attempted or completed suicide 12,67 . Taking the data together, the relationship between different levels and types of gambling and suicidal thoughts and behaviors is at present incompletely understood and warrants further investigation.…”
Section: Resultsmentioning
confidence: 97%
“…n Corresponding author at: San Francisco VA Medical Center, PTSD Program proximal antecedents-relationship problems, work problems, and legal issues (Bush et al, 2013;Crawford et al, 2009;Holmes et al, 1998;Kaplan et al, 2007Kaplan et al, , 2012Logan et al, 2012;Nock et al, 2013;Skopp et al, 2012). We predicted that there would be more similarities than differences across risk factors, particularly for mental health diagnoses, which are stable predictor of suicide across studies (Bossarte et al, 2012;Bush et al, 2013;Ilgen et al, 2012;LeardMann et al, 2013;Luxton et al, 2013;Nock et al, 2013;Skopp et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Depression has also been identified as a predominant psychiatric complaint amongst military personnel [e.g., The Iowa Persian Gulf Study Group, 1997;Slusarcick et al, 1997;Winfield and Lafferty, 1997]. In military personnel, it is a significant concern given close associations with suicide, the third leading cause of death in military populations [Holmes et al, 1998;Sentell et al, 1997], and with the unique experiences that characterize military operations (e.g., exposure to novel environments, combat-related stressors, and atypical sleep schedules) [Ferrer et al, 1995;Sutker et al, 1994]. In order to better understand the nature of depression in military personnel and to improve associated assessment and treatment strategies, it is necessary to have a measure that provides a reliable and valid representation of the construct.…”
Section: Introductionmentioning
confidence: 98%